2015
DOI: 10.1371/journal.pone.0127709
|View full text |Cite
|
Sign up to set email alerts
|

Own-Race Faces Capture Attention Faster than Other-Race Faces: Evidence from Response Time and the N2pc

Abstract: Studies have shown that people are better at recognizing human faces from their own-race than from other-races, an effect often termed the Own-Race Advantage. The current study investigates whether there is an Own-Race Advantage in attention and its neural correlates. Participants were asked to search for a human face among animal faces. Experiment 1 showed a classic Own-Race Advantage in response time both for Chinese and Black South African participants. Using event-related potentials (ERPs), Experiment 2 sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 51 publications
(85 reference statements)
2
25
1
Order By: Relevance
“…Nonetheless, studies that did include participants of several ethnicities in their experiments and used similar paradigms to ours found that regardless of the ethnicity of the participant, same-ethnicity faces captured faster attention than other-ethnicity faces (Zhou et al, 2015), and that same-ethnicity faces were recognized more successfully than other-ethnicity faces (Tanaka et al, 2004).…”
Section: G Ener Al Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Nonetheless, studies that did include participants of several ethnicities in their experiments and used similar paradigms to ours found that regardless of the ethnicity of the participant, same-ethnicity faces captured faster attention than other-ethnicity faces (Zhou et al, 2015), and that same-ethnicity faces were recognized more successfully than other-ethnicity faces (Tanaka et al, 2004).…”
Section: G Ener Al Discussionsupporting
confidence: 62%
“…An attentional preference for same‐ethnicity faces has been reliably found using other selective attention paradigms such as in eye tracking (Kelly et al, ) and visual search tasks (Zhou et al, ). For example, Zhou et al () measured selective attention when determining the presence of same‐ and other‐ethnicity faces among exogenous distractors in a visual search task. Participants displayed a same‐ethnicity advantage such that same‐ethnicity faces captured attention more efficiently than other‐ethnicity faces, a bias that occurs relatively early in development (Kelly et al, ).…”
Section: Experiments 1 Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a recent study of the effect of same-race bias on face recognition, Zhou et al (2015) presented arrays containing human and non-human faces. Participants were asked simply to determine if a human face was present in an array of faces.…”
Section: Discussionmentioning
confidence: 99%